2007
DOI: 10.1021/es061921y
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation of Ciprofloxacin Speciation at the Goethite−Water Interface

Abstract: We investigated ciprofloxacin (a fluoroquinolone antibiotic) speciation as a function of pH in aqueous solution and in the presence of dissolved ferric ions and goethite using ATR-FTIR and UV-vis spectroscopy. The presence of dissolved and surface bound ferric species induced the deprotonation of the ciprofloxacin carboxylic acid group at pH < pKa1. The resultant ciprofloxacin zwitterions appeared to interact via both carboxylate oxygens to form bidentate chelate and bridging bidentate complexes within colloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
86
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 22 publications
13
86
0
Order By: Relevance
“…Assignments of the remaining vibrations observed in Fig. 1 are as follows: C O stretch of ketone group (1629 cm −1 ), and coupled carboxylic acid C O stretch ( COOH ) and O-H deformation (ı C OH ) (1274 cm −1 ) [3,4]. The interaction between Nor and K + -montmorillonite was investigated by comparing the spectra of sorbed Nor with those of Nor in solution.…”
Section: Influence Of Solution Ph On Nor Sorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assignments of the remaining vibrations observed in Fig. 1 are as follows: C O stretch of ketone group (1629 cm −1 ), and coupled carboxylic acid C O stretch ( COOH ) and O-H deformation (ı C OH ) (1274 cm −1 ) [3,4]. The interaction between Nor and K + -montmorillonite was investigated by comparing the spectra of sorbed Nor with those of Nor in solution.…”
Section: Influence Of Solution Ph On Nor Sorptionmentioning
confidence: 99%
“…Thus, their sorption behavior in the environment is significantly different from that of other hydrophobic organic chemicals (HOCs). Past studies examined pH-dependent sorption of antibiotics onto clays [2], aluminum oxides [3,4], and amorphous iron oxides [3], goethite [4], soil and soil minerals [5,6], and carbon nanotubes [7]. The proposed mechanisms included cation exchange and cation bridging [8], surface complexation [3,4], and hydrophobic interaction [7].…”
Section: Introductionmentioning
confidence: 99%
“…These antibiotics can interact strongly with clay, nature organic matter and metal oxides Karthikeyan, 2005, 2008;Trivedi and Vasudevan, 2007;Mackay and Seremet, 2008). Simon (2005) also found that loosely bound antibiotics are subject to desorption and might be biologically active, which suggests that the sediment may be a pollution source of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Current understanding of Cip and tetracycline sorption to soils and soil minerals has revealed similarities in the mechanisms, with both compound classes being sorbed onto aluminosilicate clays either via cation exchange and cation bridging (3,(8)(9)(10) or via surface complexation (4,5,11,12). However, the exact mechanism of surface complexation is unknown.…”
Section: Introductionmentioning
confidence: 99%